2020
DOI: 10.1080/02813432.2020.1753348
|View full text |Cite
|
Sign up to set email alerts
|

Why do doctors in Norway choose general practice and remain there? A qualitative study about motivational experiences

Abstract: Objective: To explore experiences motivating doctors to become and remain GPs. Design and contributors: Qualitative analysis of written responses from an open-ended question about motivational experiences posted on an internet discussion list for GPs in Norway. Texts from 25 contributors were analysed with Systematic Text Condensation, supported by theories about calling as motivation. Results: Analysis revealed numerous aspects of motivation to become and remain a general practitioner. Inspirations from early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…They suggested that the possibility for employees to choose their own activity during breaks is as important as what they actually do during the break. Also, in a qualitative study exploring why general practitioners remain at their jobs, the room for autonomy and independence was emphasised [33]. In our study, the feeling of having influence was important and one of the areas of improvement during the intervention period.…”
Section: Findings Compared To Other Studies and Literaturementioning
confidence: 72%
“…They suggested that the possibility for employees to choose their own activity during breaks is as important as what they actually do during the break. Also, in a qualitative study exploring why general practitioners remain at their jobs, the room for autonomy and independence was emphasised [33]. In our study, the feeling of having influence was important and one of the areas of improvement during the intervention period.…”
Section: Findings Compared To Other Studies and Literaturementioning
confidence: 72%
“…28 This finding echoes the biopsychosocial model that highlights psychological support while managing patients in clinical care. 5 Physicians' emotional support can benefit patients in several ways, which may lead to better patients' trust. 20 Patients with better emotional support from their physicians had better adherence to medications and treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…PCPs' perceived patients' trust was a gratifying feature of general practice and is of high importance for enhancing physicians' morale. 5 According to the Chinese National Health Service Survey, with the decline in medical personnel's self-perceived patients' trust and respect, from 2008 to 2013, their perception of patient satisfaction and professional sense of honour dropped by 5.8 percentage and 15.5 points, respectively. 6 Recognition of patients' trust helps to build a rewarding doctor-patient relationship from physicians' perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partisipan dalam penelitian ini lahir antara tahun 1992-1994, masuk dalam karakter akhir milineal atau awal generasi Z. Konteks generasi Z yang memiliki pilihan pribadi 19 dengan daya refleksi yang unggul pada values (nilainilai yang rewarding secara personal) serta dorongan teman sekitar atau lingkungan mewarnai keputusan pemilihan karier mereka. 20 Mayoritas partisipan dalam penelitian ini menyatakan bahwa mereka sudah memiliki kepercayaan diri dan pandangan yang jelas terhadap karier di masa depan. Keyakinan dan kepercayaan diri mengindikasikan kemampuan melakukan perencanaan karier.…”
Section: Gambar 1 Peta Konsep Hasil Analisis Kualitatif Alasan Memilih Karier Nonklinisiunclassified